Sabbatical Leave Report. - Latorre, Sobeira (2015)
The objective of my sabbatical leave was to make progress on a book project tentatively entitled: "In conversation: Dominican women writers speak." This project is a book of interviews with contemporary women writers from the Dominican Republic as well as writers who identify themselves as Domincan-American...
Keywords: dept.wll; faculty_collection; sabbatical_report